Ruxolitinib for polycythemia vera and essential thrombocytosis: a single-center experience - Ekinci, O.; Merter, M. (Pergamon-Elsevier Science Ltd, 2019)
[Abstract Not Available]
10th Eurasian Hematology Oncology Congress -- OCT 08-11, 2019 -- Istanbul, TURKEY